1999
DOI: 10.1161/01.cir.99.24.3188
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Collateral Vessel Development Associated With Reduced Expression of Vascular Endothelial Growth Factor in ApoE −/− Mice

Abstract: These findings thus underscore the extent to which hyperlipidemia adversely affects native collateral development but does not preclude augmented collateral vessel growth in response to exogenous cytokines. Moreover, results obtained in the apoE-/- and athymic nude mice imply a critical role for infiltrating T cells as a source of VEGF in neovascularization of ischemic tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
204
5
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(220 citation statements)
references
References 19 publications
7
204
5
4
Order By: Relevance
“…The murine HLI model is frequently used for studying the angiogenic potential of injected cells. Therefore, after operative resection of one of the femoral artery in athymic mice, in which angiogenesis is characteristically impaired (47), labeled cells, for example, EPCs, are injected. To follow the angiogenetic potential of the injected cells over time, laser Doppler perfusion imaging is used to measure blood flow.…”
Section: Functional Analysismentioning
confidence: 99%
“…The murine HLI model is frequently used for studying the angiogenic potential of injected cells. Therefore, after operative resection of one of the femoral artery in athymic mice, in which angiogenesis is characteristically impaired (47), labeled cells, for example, EPCs, are injected. To follow the angiogenetic potential of the injected cells over time, laser Doppler perfusion imaging is used to measure blood flow.…”
Section: Functional Analysismentioning
confidence: 99%
“…The link between apoE4 and pathological vascularization has not been well elucidated; however, apoE4 is accepted as a risk factor for atherosclerosis (Altenburg et al, 2007;Knouff et al, 1999;Scuteri et al, 2005). In animal model studies, murine apoE is known to influence pathological vascularization (Couffinhal et al, 1999;Pola et al, 2003). Evidence suggests that mice lacking apoE (ApoE−/−) have impaired angiogenesis, as well as a reduced capacity to upregulate VEGF, a prototypical angiogenic cytokine, in response to ischemic stimuli (Couffinhal et al, 1999;Pola et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In animal model studies, murine apoE is known to influence pathological vascularization (Couffinhal et al, 1999;Pola et al, 2003). Evidence suggests that mice lacking apoE (ApoE−/−) have impaired angiogenesis, as well as a reduced capacity to upregulate VEGF, a prototypical angiogenic cytokine, in response to ischemic stimuli (Couffinhal et al, 1999;Pola et al, 2003). We are aware of no reports confirming whether or not human apoE3 or apoE4 influences corneal neovascularization following ocular HSV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…tissue necrosis) in old animals 8,11 and in animals with compromised immune system. 9,12 Diminished angiogenesis in these animal models corresponded with decreased expression of VEGF. 8,9,13 Interestingly, substituting VEGF by exogenously delivered protein or gene has not shown therapeutic benefit in either aged mice 11 or in balb/c mice, 12 unlike in other mouse models.…”
Section: Introductionmentioning
confidence: 87%
“…5 In the presence of cardiovascular risk factors, including advanced age, angiogenesis is impaired, which may contribute to the increased severity of cardiovascular diseases in this patient population. [6][7][8][9][10] Studies in experimental mouse models of hindlimb ischemia demonstrated impaired revascularization and CLI like symptoms (i.e. tissue necrosis) in old animals 8,11 and in animals with compromised immune system.…”
Section: Introductionmentioning
confidence: 99%